1999
DOI: 10.1002/1531-8249(199908)46:2<217::aid-ana11>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral subthalamic or pallidal stimulation for Parkinson's disease affects neither memory nor executive functions: A consecutive series of 62 patients

Abstract: There is a renewal of interest in surgical approaches including lesions and deep brain stimulation directed at motor subcorticofrontal loops. Bilateral lesioning presents a far greater risk of adverse effects, especially cognitive impairment. Furthermore, the main advantages of the stimulation procedure over lesioning are adaptability and reversibility of effects. The aim of this study was to assess the influence of bilateral stimulation of the subthalamic nucleus or internal globus pallidus on memory and exec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
252
1
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(292 citation statements)
references
References 32 publications
21
252
1
9
Order By: Relevance
“…[30][31][32][33][34] These studies, with few exceptions, 20,[35][36][37][38][39] have observed small and circumscribed cognitive changes, most often in verbal fluency (timed oral word generation according to different phonemic or semantic constraints). 16,17,37,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Even among studies reporting more widespread cognitive declines there is disagreement as to the clinical meaningfulness of these changes. Alegret and co-workers 35 interpreted the changes not to be of clinical significance, in contrast to Saint-Cyr et al 38 and Smeding et al 39 As many of the neuropsychological studies of STN DBS have small sample sizes, greater weight should be given to the five controlled neuropsychological studies (excluding studies limited to language or cognitive screening evaluations), even though each has significant methodological and/or conceptual limitations.…”
Section: Pallidal Deep Brain Stimulationsupporting
confidence: 91%
See 2 more Smart Citations
“…[30][31][32][33][34] These studies, with few exceptions, 20,[35][36][37][38][39] have observed small and circumscribed cognitive changes, most often in verbal fluency (timed oral word generation according to different phonemic or semantic constraints). 16,17,37,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Even among studies reporting more widespread cognitive declines there is disagreement as to the clinical meaningfulness of these changes. Alegret and co-workers 35 interpreted the changes not to be of clinical significance, in contrast to Saint-Cyr et al 38 and Smeding et al 39 As many of the neuropsychological studies of STN DBS have small sample sizes, greater weight should be given to the five controlled neuropsychological studies (excluding studies limited to language or cognitive screening evaluations), even though each has significant methodological and/or conceptual limitations.…”
Section: Pallidal Deep Brain Stimulationsupporting
confidence: 91%
“…[16][17][18] Nonetheless, a small minority of patients may develop cognitive morbidity. One case with magnetic resonance imaging (MRI)-confirmed electrode location had significant executive dysfunction ensuing from bilateral GPi DBS; importantly, when the stimulators were turned off, the impairment was partially reversed, thereby suggesting a direct role of stimulation in the neuropsychological deficit.…”
Section: Pallidal Deep Brain Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuropsychological assessment confirmed a worsening of phonological verbal fluency after STN-DBS, as already described in the short-term [17].…”
Section: Discussionmentioning
confidence: 99%
“…110 Long-term, treatment-resistant postoperative apathy tends to develop in association with levodopa-resistant frontal dysexecutive syndrome, and can be explained by diff use cortical synucleinopathy 2,10,50,56,111,112 rather than by STN-DBS on its own. Although dementia might be a part of Parkinson's disease progression, 113,114 in the young and largely cognitively preserved populations of patients with Parkinson's disease who are generally selected for deep brain stimulation, overall cognition, including frontal dysexecutive syndrome, is relatively stable 115,116 in the fi rst years after STN-DBS, although in a small proportion of patients, surgery itself can induce cognitive deterioration. 117 Surgical treatment of Parkinson's disease has given rise to a new phenotype of patients with advanced Parkinson's disease who have little akinesia, no tremor or rigidity, and little dyskinesia, and are mainly disabled by frontal dementia, apathy, and levodoparesistant axial motor features.…”
Section: Apathy After Deep Brain Stimulation In Parkinson's Diseasementioning
confidence: 99%